Ideological Affirmation of Postmodern Indian English Novelists with Right-Wing Propaganda in the Contemporary Era - Kamble, Dattatraya Shavarappa; Gaikwad, Pravin Babasaheb (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
This critical note interrogates the increasingly complex and often troubling relationship between a select segment of Indian English novelists, their literary output, and the ideological apparatus of the contemporary right-wing ecosystem in India. Moving beyond the well-documented critiques of Hindutva by progressive writers, it focuses on authors and novels that, either implicitly or explicitly, affirm key tenets of right-wing propaganda. This affirmation is analyzed not as crude polemic but as a sophisticated literary encoding of ideological positions—through narrative structure, character archetype, historical imagination, and the construction of civilizational identity, trauma, and heroism. By critically examining the works of authors such as Vishnu Sharma (Amish Tripathi), Ashwin Sanghi, and aspects of Chitra Banerjee Divakaruni’s recent oeuvre, this paper argues that a subset of Indian English fiction has transitioned from a critical, secular, or cosmopolitan tradition to one that actively legitimizes, sanitizes, and disseminates a majoritarian, neo-traditionalist worldview. This shift aligns with what scholars’ term “soft Hindutva” and the cultural project of re-mythologization, serving to naturalize right-wing narratives for a globalized, English-speaking elite and middle class. The analysis delves into thematic preoccupations with a glorified Vedic Golden Age, the monolithic victimhood of the Hindu, the demonization of the Islamic “other,” and the rise of the muscular, devotional hero. Ultimately, this note posits that this literary trend represents a significant cultural capture, where the tools of liberal storytelling are repurposed to advance an illiberal political project, blurring the lines between cultural revivalism and majoritarian propaganda.